Analisis Profesionalisme, Independensi dan Pengalaman, Terhadap Pencegahan Kecurangan Perusahaan - Frenky Situmorang (Outline Journal of Management and Accounting, 2023)
The purpose of this study is to determine how much influence the Experience, Independence, and Professionalism Against Cheating Prevention. The research methodology used is quantitative descriptive method, the unit of analysis in this study is PT. Sumatra Sarana Sekar Sakti and its observation unit are Internal Auditors from PT. Sumatra Sarana Sekar Sakti. The population in this study is the Internal Auditor of PT. Sumatra Sarana Sekar Sakti as many as 30 respondents. The technique of determining the number of samples used in this study is a saturated sample and amounting to 30 respondents. The research method used is the technique of data collection through the distribution of questionnaires conducted systematically based on research objectives. The analytical method used to solve problems and prove hypotheses is descriptive analysis and regression analysis. The results of the t test show that the Experience variable does not effect on Fraud Prevention variable, the Independence variable does not effect on Fraud Prevention variable, and the Professionalism variable has a positive and significant effect on Fraud Prevention variable. The results of the F test show that Experience, Independence and Professionalism simultaneously influence the Fraud Prevention. The coefficient of determination test results (R2) shows that Fraud Prevention is influenced by the Experience, Independence and Professionalism variables, while the remaining is explained by the influence of variables outside the model such as internal control, integrity, and anti-awareness fraud that is not discussed in this study.